Analisis Efisiensi Perusahaan Pembiayaan Di Indonesia Pada Masa Pandemik - Ahmad Rizki Harahap, Rahmat Putra Ahmad Hasibuan, Amir Hamzah Nasution, Musafran Harahap (Journal Economy and Currency Study (JECS), 2022)
This study aims to analyze the efficiency of the performance of finance companies in Indonesia during the COVID-19 pandemic starting from 2019-2021 using the Data Envelopment Analysis (DEA) approach. The type of data in this research is secondary data in the form of financial statements and annual reports of finance companies obtained from the official websites www.idx.co.id and www.ojk.go.id. The population in this study were all finance companies in Indonesia registered with the financial services authority (OJK). The sampling technique used is purposive sampling technique with a sample of 76 finance companies. The test used in this study is a non-parametric test with a Data Envelopment Analysis (DEA) model that compares the inputs and outputs of companies. The selected input variables include, fixed assets, labor costs, third party funds (DPK). While the output variables include loans, interest income, non-interest income. The results showed that the average finance company in 2019 had an efficient value and continued to increase, but at the beginning of 2020 to 2021 it experienced an inefficient decline during the covid-19 pandemic